Penta-helix Collaboration in the Development of Papua Province's Creative Economy - Bambang Tri Atmojo; Siswidiyanto Siswidiyanto; Oscar Radyan Danar (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
Disparities of development in Papua Province contrast with the level of poverty and low HDI in several Papua Province regions. Improving the welfare of the Papuans may be accomplished by implementing the concept of the creative economy, which is indicated by the creative economy's potential for national exports and increased workforce involvement. This demonstrates the possibilities that may be realized by adopting the Penta Helix Collaboration concept. A literature review method with a qualitative approach was used in this research. The Papua Provincial Government, the private sector, academics, the community, and the media are the actors in the Penta Helix Collaboration. As the initiator and mediator, the Papua Provincial Government provides policy facilities and legal guarantees for other actors to participate. The private sector can help with funding and technology transfer, the community can help with creative economy development needs, and academics can help with knowledge transfer to creative economy actors. The media plays a role in developing brand image and widely and massively promoting products to expand the market